pH-Sensitive Chitosan-Heparin Nanoparticles for Effective Delivery of Genetic Drugs into Epithelial Cells - Iuliia Pilipenko; Viktor Korzhikov-Vlakh; Vladimir Sharoyko; Nan Zhang; Monika Schäfer-Korting; Eckart Rühl; Christian Zoschke; Tatiana Tennikova (MDPI AG, 2019)
Chitosan has been extensively studied as a genetic drug delivery platform. However, its efficiency is limited by the strength of DNA and RNA binding. Expecting a reduced binding strength of cargo with chitosan, we proposed including heparin as a competing polyanion in the polyplexes. We developed chitosan−heparin nanoparticles by a one-step process for the local delivery of oligonucleotides. The size of the polyplexes was dependent on the mass ratio of polycation to polyanion. The mechanism of oligonucleotide release was pH-dependent and associated with polyplex swelling and collapse of the polysaccharide network. Inclusion of heparin enhanced the oligonucleotide release from the chitosan-based polyplexes. Furthermore, heparin reduced the toxicity of polyplexes in the cultured cells. The cell uptake of chitosan−heparin polyplexes was equal to that of chitosan polyplexes, but heparin increased the transfection efficiency of the polyplexes two-fold. The application of chitosan−heparin small interfering RNA (siRNA) targeted to vascular endothelial growth factor (VEGF) silencing of ARPE-19 cells was 25% higher. Overall, chitosan−heparin polyplexes showed a significant improvement of gene release inside the cells, transfection, and gene silencing efficiency in vitro, suggesting that this fundamental strategy can further improve the transfection efficiency with application of non-viral vectors.